Species boundaries and taxonomy of the African river frogs (Amphibia: Pyxicephalidae: Amietia) - Channing, A.; Dehling, J.m.; Lötters, S.; Ernst, R. (Zootaxa, 2016)
A molecular phylogeny of the Afrotropical anuran genus Amietia based on 323 16S sequences indicates that there are 19 species, including four not yet described. No genetic material was available for the nominal A. inyangae. We consider them to represent full species, and define them based on 16S genetic distances, as well as differences in morphology, tadpoles and advertisement call where known. An analysis based on two mitochondrial and two nuclear genes (12S, 16S, 28S and tyrosinase exon 1), from 122 samples, confirmed the phylogenetic relationships suggested by the 16S tree. We recognise and (re-) describe the following species: Amietia angolensis (Bocage, 1866), A. chapini (Noble, 1924), A. delalandii (Duméril & Bibron, 1841), A. desaegeri (Laurent, 1972), A. fuscigula (Duméril & Bibron, 1841), A. hymenopus (Boulenger, 1920), A. inyangae (Poynton, 1966), A. johnstoni (Günther, 1893), A. moyerorum sp. nov., A. nutti (Boulenger, 1896), A. poyntoni Channing & Baptista, 2013, A. ruwenzorica (Laurent, 1972), A. tenuoplicata (Pickersgill, 2007), A. vandijki (Visser & Channing, 1997), A. vertebralis (Hewitt, 1927), and A. wittei (Angel, 1924). Three further candidate species of Larson et al. (2016) await formal naming. We provisionally regard A. amieti (Laurent, 1976) as a junior synonym of A. chapini (Noble, 1924). Amietia lubrica (Pickersgill, 2007) is shown to be a junior synonym of A. nutti, while A. quecketti (Boulenger, 1895) is shown to be a junior synonym of A. delalandii (Duméril & Bibron, 1841), and A. viridireticulata (Pickersgill, 2007) is placed as a junior synonym of A. tenuoplicata (Pickersgill, 2007). On the basis of similarity of 16S sequences, we assign A. sp. 1, A. sp. 3 and A. sp. 6 of Larson et al (2016) to the nomina A. chapini (Noble, 1924), A. desaegeri (Laurent, 1972), and A. nutti (Boulenger, 1896) respectively.